SARRÓ Ramon: Inventing an African Alphabet: Writing, Art, and KongoCulture in the DRC. Cambridge: Cambridge University Press. (pb. $30.00- 9781009199490). 2023, xvi–199 pp.' - (:unkn) unknown (My University, 2024)
A book review of SARRÓ Ramon: Inventing an African Alphabet: Writing, Art, and Kongo Culture in the DRC. Cambridge: Cambridge University Press
Keywords: African Research